Panduan Training untuk Operator Test Room di PT “X” - Sherly Silvia Dewi; Felecia Felecia (Jurnal Titra, 2017)
This study has been done to create training guide for operator test room AB. There is no clear training guide and only rely on work instruction (WI) during training makes the operator not have clear guidelines. This project use direct observation in the field and Q&A against the parties which have relation with test room AB. And then, the result of the observation will be organized become training guide for operator test room AB. This training guide is expected to get an effective and efficient training which can increase number of competent operators.